2020
DOI: 10.1371/journal.pone.0242152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pro-inflammatory cytokines in frail Tunisian older adults

Abstract: The present study was undertaken to evaluate serum levels of pro-inflammatory cytokines in Tunisian older adults and to examine the relationships between inflammatory marker levels, geriatric, and biochemical parameters. A cross-sectional study was conducted in a population of Tunisian older adults (N = 141, aged 65 and over). Patients were recruited from the Department of Internal Medicine, Fattouma Bourguiba University Hospital (Monastir, Tunisia) and from a nursing home (Sousse, Tunisia). Comprehensive geri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 48 publications
(61 reference statements)
1
8
0
Order By: Relevance
“…In the randomized PolSenior study, which investigated 4979 elderly participants from Poland, a relationship between markers of inflammation (IL6 and CRP) and frailty were shown [94]. What is more, Hammami et al showed positive associations between frailty score and pro-inflammatory markers: CRP, IL-6, IL-8 and TNF-α [95]. Moreover, in this study, the relationship between CRP and frailty was still strong and significant after adjusting for age.…”
Section: Oxidative Stress and Inflammation Markers In Elderly Individ...supporting
confidence: 44%
“…In the randomized PolSenior study, which investigated 4979 elderly participants from Poland, a relationship between markers of inflammation (IL6 and CRP) and frailty were shown [94]. What is more, Hammami et al showed positive associations between frailty score and pro-inflammatory markers: CRP, IL-6, IL-8 and TNF-α [95]. Moreover, in this study, the relationship between CRP and frailty was still strong and significant after adjusting for age.…”
Section: Oxidative Stress and Inflammation Markers In Elderly Individ...supporting
confidence: 44%
“…The present study confirmed the relationship between the incidence of frailty syndrome and a greater mean number of diseases, represented by the medications taken, and the duration of the diseases. Cognitive impairment and depression symptoms have been shown in a study conducted in Turkey by Hammami et al ( 36 ) to be a factor that increases the occurrence of frailty syndrome. A study by Lenardt et al showed that physical disability, loss of independence, and increased frequency of hospitalization and institutionalization are all consequences of frailty syndrome that reduce the quality of life of older people ( 37 ).…”
Section: Discussionmentioning
confidence: 95%
“…Further, the MNA ® appears useful to measure frail older persons, especially when the MNA ® is between 17 and 23.5 (27,286,303,335,336). Malnutrition and physical frailty seem to be strongly related, however, they should be assessed separately within the geriatric assessment (313,317,326,(337)(338)(339)(340)(341).…”
Section: Mna ® Use In Clinical Researchmentioning
confidence: 99%